Pseudo-Thinking in Solving Mathematical Problems Based on Field Independent Cognitive Style - Zulfikry Ahmad Rifqy; Abdul Gaffar; Erni Ekafitria Bahar (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Pseudo-truth thinking often serves as an implicit obstacle in mathematics education, since pupils can provide correct answers without fully comprehending its basic principles. This issue necessitates deeper comprehension, especially for pupils' psychological traits, including cognitive style. This study seeks to elucidate the pseudo-truth cognitive process exhibited by individuals with a Field Independent (FI) cognitive style when addressing arithmetic issues among eighth-grade students at Muhammadiyah Middle School in Parepare. This study used a descriptive qualitative approach. The subject of the study was one student with a FI cognitive style selected through the Group Embedded Figures Test (GEFT). Supporting instruments included a mathematics problem-solving test and clinical interview guidelines. Data validity was guaranteed through method and time triangulation, while data analysis was carried out through the stages of data condensation, data presentation, and conclusion drawing. The research shows that FI participants thought pseudo-analytically. Subjects can isolate problem variables yet intentionally use logic to get perfect responses. The Pythagoras formula and calculation method were disconnected, resulting in severe exponent mistakes. The individuals thought they answered the problem correctly because they followed the mathematical "format," even if the steps were illogical. Metacognitive control and algorithm memorization were also areas of weakness, demonstrating conceptual comprehension problems. This study suggests that educators should be more aware that students' correct answers may not reflect their conceptual knowledge. These findings can help teachers create learning interventions that detect and correct pseudo-thinking based on students' cognitive styles.